Analysis of Sports Brand Marketing Strategy Based on STP Theory: Lululemon as an Example - Bi, Ran (Transactions on Social Science, Education and Humanities Research, 2024)
In the sports apparel market continues to slump, the global retail industry is in a weak state of the environment, Lululemon started with yoga clothing but the scenery is unique, and become a sports brand comparable to Adidas and Nike. This paper analyzes Lululemon’s successful brand strategy from three aspects: STP strategy, sports brand management and DTC marketing, and puts forward constructive suggestions on Lululemon’s current market sinking. In the operation of the Chinese market, lululemon’s successful brand function positioning strategy plays a decisive role, which is divided into market segmentation, target and positioning. Market segmentation analyzes lululemon consumer groups from demographic factors and psychological factors. Lululemon is more optimistic about the sales situation in Chinese first-tier cities, and is planning the expansion of offline stores in second-tier cities. Taking Chengdu as an example, it analyzes its market share. Through unique selling points, lululemon has solved the pain points, and consumers’ spending power has been improved.